Modelling and Production of Injection Moulded Polyvinylchloride--Sawdust Composite - C.O. Aliyegbenoma; J.A. Apkobi; D.D. Olodu (Journal of Applied Sciences and Environmental Management)
This study focused on the modeling and production of the injection  moulded Polyvinylchloride-Sawdust (PVC-sawdust) composite. The PVC material and sawdust were mixed together to form a homogenous mixture with various percentage composition by volume as recommended by the central composite design (CCD). The two screw plunger injection moulding machine with maximum clamping force of 120 tons and shot capacity of 3.0oz was used to produce Polyvinylchloride-Sawdust (PVC-Sawdust) composite at various temperature. The produced composites were evaluated for their mechanical properties which included tensile strength, proof stress, percentage elongation and flexural strength. The response surface methodology (RSM) was used to determine the effect of the interaction of temperature, material type and percentage by volume of material on the mechanical properties of the produced PVC-sawdust composite. The optimization results for PVC-Sawdust composite shows that the tensile strength, proof stress, flexural strength and flexural modulus were maximized with values of 43.70MPa, 48.38MPa, 61.41MPa and 3.42GPa respectively obtained at barrel temperature of 224.65oC and polymer level of 61.46% respectively while percentage elongation and average deflection were minimized with values of 65.43% and 4.23 cm respectively. A desirability of 0.952 was obtained which shows the adequacy of the model terms. The models were validated using coefficient of determination (R2). The coefficient of determination (R2) obtained ranged from 0.9213 (92.13%) to 0.981 (98.10%) which indicates that a substantial good fit was achieved by the model developed. The values obtained from the validation of these models were therefore found to be satisfactory, and shows good predictability of the model and its adequacy.